Complications of extraperitoneal robot-assisted radical prostatectomy in high-risk prostate cancer: A single high-volume center experience - Paladini, Alessio; Cochetti, Giovanni; Felici, Graziano; Russo, Miriam; Saqer, Eleonora; Cari, Luigi; Bordini, Stefano; Mearini, Ettore (Frontiers in Surgery, 2023)
Introduction The role of robot-assisted radical prostatectomy (RARP) in high-risk prostate cancer (PCa) has been debated over the years, but it appears safe and effective in selected patients. While the outcomes of transperitoneal RARP for high-risk PCa have been already widely investigated, data on the extraperitoneal approach are scarcely available. The primary aim of this study is to evaluate intra- and postoperative complications in a series of patients with high-risk PCa treated by extraperitoneal RARP (eRARP) and pelvic lymph node dissection. The secondary aim is to report oncological and functional outcomes. Methods Data of patients who underwent eRARP for high-risk PCa were prospectively collected from January 2013 to September 2021. Intraoperative and postoperative complications were recorded, as also perioperative, functional, and oncological outcomes. Intraoperative and postoperative complications were classified by employing Intraoperative Adverse Incident Classification by the European Association of Urology and the Clavien–Dindo classification, respectively. Univariate and multivariate analyses were performed to evaluate a potential association between clinical and pathological features and the risk of complications. Results A total of 108 patients were included. The mean operative time and estimated blood loss were 183.5 ± 44 min and 115.2 ± 72.4 mL, respectively. Only two intraoperative complications were recorded, both grade 3. Early complications were recorded in 15 patients, of which 14 were of minor grade, and 1 was grade IIIa. Late complications were diagnosed in four patients, all of grade III. Body mass index (BMI) > 30 kg/m2, Prostate-Specific Antigen (PSA) > 20 ng/mL, PSA density >0.15 ng/mL2, and pN1 significantly correlated with a higher rate of overall postoperative complications. Moreover, BMI >30 kg/m2, PSA >20 ng/mL, and pN1 significantly correlated with a higher rate of early complications, while PSA >20 ng/mL, prostate volume <30 mL, and pT3 were significantly associated with a higher risk of late complications. In multivariate regression analysis, PSA >20 ng/mL significantly correlated with overall postoperative complications, while PSA > 20 and pN1 correlated with early complications. Urinary continence and sexual potency were restored in 49.1%, 66.7%, and 79.6% of patients and in 19.1%, 29.9%, and 36.2% of patients at 3, 6, and 12 months, respectively. Conclusions eRARP with pelvic lymph node dissection in patients with high-risk PCa is a feasible and safe technique, resulting in only a few intra- and postoperative complications, mostly of low grade.